Views of Psychosocial and Organizational Dimensions: The Case of Two Elementary School Leaders - Liz Barnitz; Sharon Conley (International Journal of Educational Leadership and Management, 2020)
Using a case study approach, the authors explored psychosocial and organizational dimensions of leadership among two elementary school leaders (principals) in Southern California. At each school, interviews with the school's principal as well as two key informants were conducted, and we analyzed the findings based on principals' mental models, self-efficacy, and immunities to change. Using Kellar and Slayton's leadership framework, we considered how psychosocial and organizational leadership contexts fostered conditions to promote organizational change. The findings for this study highlight some of the conditions principals believed were important for organizational improvement as well as challenges faced.  Findings indicate that psychological and organizational dimensions reveal complexities of educational leadership by providing a fine-grained portrait of leadership and organizational learning. A study implication is that leaders must not only have time for reflection but also be open to identifying their immunities that may deter efforts at growth and change. Research directions are proposed, including further exploration of how leaders' efforts are shaped by their contexts as well as particular challenges experienced in the role.